Relationship between comorbid factors and mortality of inhalation trauma patients in Wahidin Sudirohusodo Hospital, Makassar - Afianto, Nurhidayat; Rieuwpassa, A. J.; Seweng, Arifin; Lawile, Alwi (International Journal of Research in Medical Sciences, 2019)
Background: Inhalation trauma is the leading cause of death in burn patients. Inhalation trauma is caused mainly by inhalant poisons such as smoke, gas and steam. Many patients die immediately at the scene due to inhalation trauma. The purpose of this study was to determine the relationship between comorbid factors and mortality rates in patients with inhalation trauma. Methods: The research design was analytical research method with cross sectional design. The study sample consisted of 26 people (51.0%) inhalation trauma and 25 people (49.0%) without inhalation trauma obtained by consecutive sampling. Results: There was a significant relationship between inhalation trauma and death outcomes (p<0.001). The proportion of deaths in inhalation trauma (65.4%) was significantly higher than in nonhaled trauma (16.0%). There was no significant relationship between DM and outcome (p>0.05). There was no significant relationship between hypertension and outcome of death (p>0.05). There is a significant relationship between onset and outcome (p<0.05). The proportion of deaths at <24 hours onset (35.6%) was significantly lower than at onset >24 hours (83.3%). The mean blood glucose level of dead patients was higher than that of alive, which was 124.4 compared to 114.9 but was not statistically significant (p>0.05). Both the mean systole and diastole pressures of the dead patients showed significantly lower results than that of alive, i.e., the mean systole was 101.2 compared to 114.1 (p<0.05) and the mean diastole was 62.2 versus 71.4 (p<0.05). Conclusions: According to the results of the study, it was found that there was a relationship between the onset of more than 24 hours, high GDS levels, and lower blood pressure to mortality.